(untitled) (Research, Society and Development, 2020)
Water is the natural resource most likely to impose limits on development in many parts of the world. The deterioration of its quality, caused by untreated effluent discharges, tends to be a threat to public health. In this sense, this work aims to evaluate the performance of the Sewage Treatment Station of Clube Náutico Alvorada, Caratinga / MG, in its start-up process. Laboratory analyzes were performed to determine the efficiency of the anaerobic treatment system in its start-up process in the treatment of tourist wastewater. The parameters analyzed were pH, Temperature, Conductivity, COD, BOD, Dissolved Solids, Suspended Solids and Sedimentable Solids. The average overall efficiencies for BOD and COD were, respectively, 49.50 and 59.96%. The performance of the WWTP can be explained by the variation of the effluent flow and organic load. The stability of the system has not yet been fully achieved, but its treatment has shown good results.